El papel de la comunicación en la rehabilitación, educación e integración de personas con discapacidad en Riobamba, año 2020. - Méndez Pomatoca, Jessica Germania (2022)
This research analyzes the role of communication in rehabilitation, education and integration of people with disabilities in Riobamba during 2020. Since communication is a valuable tool to recognize the rights of this social group, it has had the support of institutions that address their service to meet the needs of people with different types of disabilities, who require the utilization of adequate communication processes to their rights. Data obtained determine that the institutions had a special interest in maintaining internal relations during the study period, so that they held face-to-face meetings which were replaced by videoconferences in the second quarter of 2020. Social networks constituted the main means of communication, so they had adequate tools for the attention group in each entity, allowing people with disabilities to have access to information without violating their interests, especially because they are not able to rehab out their daily activities in their respective institutions. It should be emphasized that people with disabilities are the main source of information and they have demonstrated that they are satisfied with the services they receive. It is worth mentioning that the expert's opinion for whom communication requires the use of an inclusive language in which each person is valued, therefore, the communication with people who have disabilities must be framed in a respectful way, providing them with appropriate conditions for the rehabilitation.